PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NHT TERHADAP HASIL BELAJAR MEMILIH MAKANAN BERGIZI SISWA KELAS III SDN 064976 MEDAN TEMBUNG - Wassalwa Sitorus, Manna; Usman, Khairul; Tamba, Robenhart; Winara; Sidik Siregar, Fajar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the problem of low learning outcomes in choosing nutritious food for students because students are more interested in practical learning, consider theoretical learning boring and students pay less attention to teacher explanations so they do not understand the learning material. This study aims to determine the effect of the NHT type cooperative learning model on the learning outcomes of choosing nutritious food for grade III students of SDN 064976 Medan Tembung. The type of research is a quantitative research method with a quasi-experimental research design with a nonequivalent control group design model. The research sample consisted of 2 classes, namely the experimental class (IIIA) consisting of 21 students and the control class (IIIB) consisting of 21 students. The instrument used in this study was a multiple-choice test. The data analysis techniques used were the normality test, homogeneity test and t-test processed using SPSS 30. Based on the results of the study, it was found that students in the experimental class obtained a higher average score of 85.238, while the average score of the control class was 71.667. From the calculation results using SPSS assistance, it was obtained t-count> t-table (5.265> 2.079) with a significance level of 0.000 which means <0.05 (0.000 <0.005). Thus H0 is rejected and Ha is accepted, which means that it can be concluded that there is an influence of the implementation of the NHT type cooperative model on the learning outcomes of choosing nutritious food for grade III students of SDN 064976 Medan Tembung.